The effect of seasonal variation on the delivery rate: a retrospective study - Pal, Reena; Gandotra, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: We are living in a second most populated country in the world where many social, cultural and ecological processes and events occur regularly every year. These seasonal processes influence many vital rates including birth rates. The objective of this study was to assess the effect of seasonal variation on the delivery rate in tertiary care centre. Methods: A retrospective descriptive study carried out in Government Doon Medical College Dehradun. We extracted total number of delivery over five years period from hospital records (2012-2016) and analyzed the figures for monthly variation in delivery rates. This was repeated for a standardized 30-day month and the findings compared. Results: The total number of deliveries during the study period were 43,892 with an average of 3,657 deliveries per month. The highest rate of delivery was in the August month and lowest one was in the month of April. The monthly distribution of delivery rate also showed sinusoidal pattern. Conclusions: There is significant seasonal variation in monthly distribution of delivery rate. There are maximum conception rates are in winter season and minimum conception is in summer season. These findings will prove valuable in health system planning and in the interpretation of seasonal variations in other reproductive parameters.